Private security in Africa From the global assemblage to the everyday - Higate, Paul; Utas, Mats (Africa Now, 2017)
Across Africa, growing economic inequality, instability and urbanization have led to the rapid spread of private security providers. While these PSPs have already had a significant impact on African societies, their impact has so far received little in the way of comprehensive analysis. Drawing on a wide range of disciplinary approaches, and encompassing anthropology, sociology and political science, Private Security in Africa offers unique insight into the lives and experiences of security providers and those affected by them, as well as into the fragile state context which has allowed them to thrive. Featuring original empirical research and case studies ranging from private policing in South Africa to the recruitment of Sierra Leoneans for private security work in Iraq, the book considers the full implications of PSPs for security and the state, not only for Africa but for the world as a whole.